Frequency effect in short-beam shear fatigue of a glass fiber reinforced polyester composite - Kotik, Hector Guillermo (2016)
The effect of loading frequency on short-beam shear fatigue behavior of a glass fiber reinforced polyester laminated was studied. Surface specimen temperature increase and macroscopic specimen damage were also evaluated. The tests were performed employing a short-beam device with three amplitude stress levels, four frequencies between 1 and 10 Hz and a shear stress ratio R = 0.1. Specimens with the smallest stress amplitude showed a fatigue life between 105 and 106 cycles and the largest stress amplitude endured approximately 104 cycles. The high stress amplitude tests produced increases in specimen temperature up to 7 °C, 4 °C and 1 °C for 10 Hz, 6 Hz and both 3 and 1 Hz respectively, while no temperature changes were measured in low amplitude tests. According to the statistical analysis performed, the changes in fatigue life were not significant for the frequency range employed in this study.